838 Pulmonary Embolectomy: Techniques and Outcomes from The Literature. (12th October 2021) - Kwan, L Y A; Lee, J; Cheung, A; Chan, J
Abstract: Aim: Pulmonary embolectomy involves the surgical removal of a thrombus from the pulmonary tree, with the most popular approaches being surgical embolectomy (SE), percutaneous pulmonary embolectomy (PPE) and minimally invasive thoracotomy (MIT). The latter two new techniques are gradually increasing in popularity in the treatment of acute pulmonary embolism (PE) due to reduced recovery times. This study aims to evaluate and compare the clinical outcomes of the three aforementioned techniques in the treatment of acute PE. Method: A literature review was performed with PUBMED to identify studies reporting these interventions. 79 papers were included, involving a total of 2445 patients. Patients' baseline characteristics and perioperative status, inpatient mortality rates and complication rates of each intervention group were individually assessed and compared. Results: Among all three interventions, SE studies demonstrated the highest in-patient mortality rate (20.8%). Patients receiving SE are also more likely to have pulmonary (2.8%) and other postoperative bleeding (7.4%). PPE patients are more likely to develop gastrointestinal bleeding and surgical site complications (4%). Scatter graph of the SE studies showed a declining trend of mortality rate over time (R²=0.50). Conclusions: All three methods are effective in treating acute PE, while SE showed a trend of decreasing mortality over time. Further research on PPE and MIT is needed to define its place in the treatment of acute PE.